Pain management and pain characteristics in obese and normal weight patients before joint replacement. Issue 5 (15th May 2014) - Thomazeau, Joséphine; Perin, Juliette; Nizard, Remy; Bouhassira, Didier; Collin, Elisabeth; Nguyen, Eliane; Perrot, Serge; Bergmann, Jean‐François; Lloret‐Linares, Célia
Abstract Rationale, aims and objectives The objective was to compare the extent of pain interference and pain medication among persons who were classified as obese [body mass index (BMI) ≥30 kg m−2] and normal weighted (BMI ≤25 kg m−2), before a hip or knee replacement surgery. Methods Patients candidate for an orthopaedic surgery were successively enrolled, over a 6‐month period, and classified in either the normal weight (BMI ≤25 kg m−2) or the obese (BMI ≥30 kg m−2) categories. Data were collected using self‐administered questionnaires with items concerning pain characteristics, pain medication and pain interference. Two standardized questionnaires were associated: the Brief Pain Inventory (BPI) and the Hospital Anxiety and Depression scale (HAD). Results Fifty‐two obese patients (candidates for 24 hip replacements and 28 knee replacements) and 51 non‐obese (23 hip replacements and 28 knee replacements) were enrolled. Obese patients suffered from a higher rate of acute pain episodes than non‐obese patients (65 versus 44%, P < 0.05). Pain interference on walking distance, sleep and relations with others was higher in obese patients. HAD score showed no significant difference between groups. The use of strong opioids and of non‐steroidal anti‐inflammatory drugs (NSAIDs) was significantly more important in obese patients (13 versus 0% and 31 versus 14%). Conclusions Obese patients suffer more significantly of unrelieved chronic pain, which lowers considerably their quality of life. Pain relief is more difficult to obtain, as it requires stronger pain medication and NSAIDs.